Pengaruh Pengendalian Internal, Moralitas Individu, Dan Ketaatan Aturan Akuntansi Terhadap Kecurangan Akuntansi Lembaga Perkreditan Desa (LPD) Se-Kecamatan Abiansemal - Noviantari, Kadek Erni; Sumadi, Ni Komang (Hita Akuntansi dan Keuangan, 2025)
Whether done on purpose or by accident, fraud is always a bad idea because it gives the perpetrators an unfair advantage in exchange for the harm they cause to others. Opportunity, pressure, and justification all play a role in the commission of fraudulent acts. The researchers wanted to see how factors like organizational culture and law enforcement influenced people's propensity toward fraud. This investigation makes use of the fraud triangle hypothesis. Abiansemal District, Badung Regency, home to 287 and 32 LPD, was the location of this study. Purposive sampling was used to select participants from a pool of 128 people for this study. Multiple linear regression analysis is used for the analysis, and a questionnaire is used to collect the data. The findings show that three factors have a negative and statistically significant impact on fraud in the accounting process: internal controls, personal morality, and adherence to accounting regulations. . Keywords: Level of Understanding of CA Certification, Career Motivation, Attitudes, Student Interests